2015
DOI: 10.1007/s00018-015-2018-8
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress mediates exocytosis of functional TRPV4 channels in endothelial cells

Abstract: Mechanosensitive ion channels are implicated in the biology of touch, pain, hearing and vascular reactivity; however, the identity of these ion channels and the molecular basis of their activation is poorly understood. We previously found that transient receptor potential vanilloid 4 (TRPV4) is a receptor operated ion channel that is sensitised and activated by mechanical stress. Here, we investigated the effects of mechanical stimulation on TRPV4 localisation and activation in native and recombinant TRPV4-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 83 publications
3
68
0
Order By: Relevance
“…Finally, it is already long known that shear stress induces currents across the plasma membrane of endothelial cells, for which mechanosensitive ion channels are responsible [7173]. Of these mechano-channels, the endothelial-expressed transient receptor potential cation channel subfamily V member 4 (TRPV4) has been recently reported to be presented at higher levels in response to flow [74], and to interact with β-catenin at cell–cell junctions [75, 76]. This hints at a potential role for cell–cell junctions in Ca 2+ -dependent signaling during adaptation to flow-derived forces.
Fig.
…”
Section: Flow Mechanosensing: Roles Of Pecam-1 and Ve-cadherinmentioning
confidence: 99%
“…Finally, it is already long known that shear stress induces currents across the plasma membrane of endothelial cells, for which mechanosensitive ion channels are responsible [7173]. Of these mechano-channels, the endothelial-expressed transient receptor potential cation channel subfamily V member 4 (TRPV4) has been recently reported to be presented at higher levels in response to flow [74], and to interact with β-catenin at cell–cell junctions [75, 76]. This hints at a potential role for cell–cell junctions in Ca 2+ -dependent signaling during adaptation to flow-derived forces.
Fig.
…”
Section: Flow Mechanosensing: Roles Of Pecam-1 and Ve-cadherinmentioning
confidence: 99%
“…For example, when contact forces are initiated in joints during running there is an immediate increase in the fluid pressure due to tissue compression, which causes the fluid to flow out of the ECM, generating shear stress and frictional drag on the matrix . Shear stress has been shown to sensitize TRPV4 activation in vascular endothelial cells, by recruiting TRPV4 to the plasma membrane . Changes of 10%‐15% in the height of chondrocytes have been measured in response to mechanical inputs, though forces will be dispersed differently in each cartilage zone, resulting in zone‐dependent shape changes in the chondron .…”
Section: Relating In Vitro Measurements Of Trpv4 and Piezo1 Activatiomentioning
confidence: 99%
“…47,50 Shear stress has been shown to sensitize TRPV4 activation in vascular endothelial cells, by recruiting TRPV4 to the plasma membrane. 51 Changes of 10%-15% in the height of chondrocytes have been measured in response to mechanical inputs, 52,53 though forces will be dispersed differently in each cartilage zone, resulting in zone-dependent shape changes in the chondron. 54…”
Section: Rel Ating In Vitro Me a Surements Of Trpv4 And Pie Zo1 Ac mentioning
confidence: 99%
“…More recently, it has been demonstrated that laminar flow- and TRPV4 agonist-induced vasodilation was impaired in aged rat mesenteric arteries, which was restored by lentivirus-mediated TRPV4 overexpression [18]. Laminar flow also sensitizes the response of TRPV4 to GSK1016790A by promoting the trafficking of TRPV4 from intracellular compartments to the plasma membrane [19]. However, it remains unknown whether pharmacological activation of TRPV4 by GSK1016790A can elicits laminar flow signaling events and prevents the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%